Food inflation and its impact on the economy of Papua New Guinea - HULAHAU, Stanis (KDI School, 2016)
This study examined the determinants of food price inflation and its impact on the economy of PNG from 2001 to 2011 (10 years) using time series data. Secondary data obtained from credible sources such as BPNG, ADB, WB, and IMF were analysed using various econometric test such as the Johansen Test for Cointergration, Augmented Dickey Fuller Test and the Vector Error Correction Model. The econometric tests revealed that there is a long run relationship (causality) between the variables real exchange rate and wheat price which significantly influenced food price inflation in PNG. There is a negative correlation between money supply and interest rate which negatively impacted food price inflation in the country. In the short run, real exchange rate, money supply, real interest rate and wheat price do not significantly affect food inflation as their corresponding p-values are greater than five percent (5%) critical value. Alternatively, there is a long run relationship or causality between GDP, real exchange rate, real interest and food price inflation. However, food inflation has a negative correlation with Real GDP in the long run. Therefore the overall findings of the study concluded that food price inflation is caused by long run relationship among the study variables and food inflation has a long run relationship with real GDP. It is recommended that the government should focus attention on the agriculture sector (food security) at the strategic and sectoral level and work in alignment with the PNG Vision 2050, National Security Policy, Monetary and Fiscal Policy, Social Protection Policy, Transport Security Policy and other food policies in PNG in order to deal with high food inflation in the country.
Thesis(Master) --KDI School:Master of Public Policy,2016